Extractionno-Photometric Determination of Diabenol - O. I. Ascalepova; I. E. Nicanorova; V. A. Anisymova (Медицинский вестник Юга России, 2011)
Purpose: To study spectral and physicochemical characteristics Diabenol’s ion-associates and extraction equilibria and to develop a method for determination of small amounts of substance in the presence of other compounds.Materials and Methods: An extraction-photometric method of analysis was chosen because it is widely used in pharmaceutical analysis and find a use in chemico-toxiological researches.Results: It was developed a method of extraction-photometric detection of dosage forms with small amounts of diabenol in the presence of substance that prevent its detection with the methods of titrimetric analysis and ultraviolet spectroscopy. The investigation showed that the use of chloroform as extraction agent of diabenol ion-associates and anionic dyes is optimal.Summary: This method makes possible to detect the basic substance with high precision and repeatability of measurements.